Multicultural Values in PAI Learning and Their Implications for Students Tolerant Attitudes - Jamaluddin Jamaluddin; Subhan Abdullah Acim; Fathurrahman Muhtar (JURNAL PENDIDIKAN IPS, 2023)
The plurality of a society is the result of multicultural inherent in their lives, at the level of education (school) plurality can be seen from the diversity of students and multicultural life in the school environment. Not only in the wider community, diversity among students also creates big problems such as the outbreak of intolerant attitudes towards fellow students. This is contrary to the multicultural values that should exist in each learner. With the embedding of these values, it will give reciprocity to the attitude of tolerance in students. This article examines multicultural values in PAI learning and the implications for students' tolerance attitudes at SMK Cendekia NW Aiklomak. This article uses the theory of multicultural values in Islamic education, the relationship between multicultural and Islamic education. This article concludes: multicultural values in Islamic education learning include: values of justice, equality, brotherhood, tolerance, ukhuwah, equality and unity. Multicultural values in PAI Learning shape students' tolerance attitudes and behaviors in the form of: respecting differences, willingness to listen to opinions, rejecting discrimination, building constructive dialogue and building cooperation.